Sleep Duration/Quality With Health Outcomes: An Umbrella Review of Meta-Analyses of Prospective Studies - Gao, Chang; Guo, Jiao; Gong, Ting-Ting; Lv, Jia-Le; Li, Xin-Yu; Liu, Fang-Hua; Zhang, Meng; Shan, Yi-Tong; Zhao, Yu-Hong; Wu, Qi-Jun (Frontiers in Medicine, 2022)
Background: To quantitatively evaluate the evidence of duration and quality of sleep as measured by multiple health outcomes. Methods: This review is registered with PROSPERO, number CRD42021235587. We systematically searched three databases from inception until November 15, 2020. For each meta-analysis, the summary effect size using fixed and random effects models, the 95% confidence interval, and the 95% prediction interval were assessed; Heterogeneity, evidence of small-study effect, and excess significance bias were also estimated. According to the above metrics, we evaluated the credibility of each association. Results: A total of 85 meta-analyses with 36 health outcomes were included in the study. We observed highly suggestive evidence for association between long sleep and increased risk of all-cause mortality. Moreover, suggestive evidence supported the associations between long sleep and 5 increased risk of health outcomes (stroke, dyslipidaemia, mortality of coronary heart disease, stroke mortality, and the developing or dying of stroke); short sleep and increased risk of overweight and/or obesity; poor sleep quality and increased risk of diabetes mellitus and gestational diabetes mellitus. Conclusions: Only the evidence of the association of long sleep with increased risk of all-cause mortality were graded as highly suggestive. Additional studies are needed to be conducted.